2007
DOI: 10.1093/jb/mvm144
|View full text |Cite
|
Sign up to set email alerts
|

Human Geranylgeranyl Diphosphate Synthase is an Octamer in Solution

Abstract: A recombinant geranylgeranyl diphosphate synthase (GGPS) was analysed to be a mixture of octamer, hexamer and dimer by gel filtration using a Superdex 200 column followed by the blue native polyacrylamide gel electrophoresis. The hexamer and dimer were each converted to an octamer by treating with dithiothreitol (DTT). When the recombinant GGPS was preliminarily treated with DTT and similarly analysed, octamer was predominantly detected with a trace amount of hexamer. The octameric form of GGPS was also suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…S4). For comparison, the human FPPS, the cotton boll weevil FPPS, and the horseradish leaf beetle GPPS/FPPS are dimers (11,12,16); human GGPPS is an octamer (17); and bovine GGPPS is a multimer of four to five units (18).…”
Section: Resultsmentioning
confidence: 99%
“…S4). For comparison, the human FPPS, the cotton boll weevil FPPS, and the horseradish leaf beetle GPPS/FPPS are dimers (11,12,16); human GGPPS is an octamer (17); and bovine GGPPS is a multimer of four to five units (18).…”
Section: Resultsmentioning
confidence: 99%
“…Work done by Kavanagh et al (2006) suggested that based on molecular weight, 5-6 monomers are associated per molecule (molecular weight 193 kDa) in solution. Sagami et al (1994) reported that GGDPS from bovine brain is a homooligomer with a monomer molecular mass of 37.5 kDa, whereas Miyagi et al (2007) reported that the active form of GGDPS in solution is an octomer and that hexamer and dimer forms On the basis of the computational modeling studies, both HG and HN can simultaneously bind to distinct but overlapping sites within the enzyme (HG with preference for the GGDP site and HN with preference for the FDP site) (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
“…However, three dimers of this enzyme join together to form a homohexamer complex, which has been described as a three-blade propeller (Figure 3B). Biochemical investigations have even described the formation of octameric complexes in solution (Miyagi et al, 2007). Despite low sequence identity (17%), the tertiary structure of hGGPPS is remarkably similar to that of hFPPS (Figure 3A).…”
Section: Human Ggpps—overall Structurementioning
confidence: 99%